Feasibility of Aluminum Waste Conversion into Automotive Emblem Accessories: Kelayakan Pengolahan Limbah Aluminium Menjadi Aksesori Lambang Kendaraan Bermotor - Dwi Febrian Aldy; Ali Akbar (Indonesian Journal of Innovation Studies, 2025)
General Background: Aluminum waste accumulation is a growing environmental concern due to its persistence and increasing volume from domestic, industrial, and construction activities. Specific Background: Recycling and reusing aluminum waste offer opportunities to reduce environmental burdens while generating value-added products, including automotive accessories. Knowledge Gap: Although aluminum waste utilization has been explored in previous studies, limited research has evaluated the feasibility of converting aluminum waste into car accessories through respondent-based pre-test and post-test assessments. Aims: This study aimed to analyze the feasibility of utilizing aluminum waste for automotive emblem accessories and to validate respondent perceptions before and after product development. Results: Questionnaire data from 97 respondents showed agreement with aluminum waste utilization during the pre-test stage and satisfaction with the resulting product during the post-test stage. Validity testing indicated significance values below 0.05, while reliability analysis produced Cronbach’s Alpha values of 0.877 for the pre-test and 0.908 for the post-test. Analysis of variance further demonstrated that the dominant respondent response in both stages was agreement with the proposed utilization and the developed product. Novelty: The study integrates aluminum waste recycling with a pre-test and post-test feasibility evaluation framework for automotive emblem production. Implications: The findings support the potential application of aluminum waste as a resource for automotive accessories and provide evidence for broader waste utilization initiatives aimed at reducing environmental pollution and creating products with economic value.Highlights: Most respondents agreed with the proposed use of recycled aluminum materials. Product evaluation indicated positive acceptance and satisfaction among participants. Statistical validation confirmed reliable and valid questionnaire outcomes in both assessment stages. Keywords: Aluminum Waste; Automotive Accessories; Feasibility Analysis; Pre-Test and Post-Test; Waste Utilization